APPLICATION OF STANDARD, INTERMEDIATE, AND ADVANCED EVIDENCE SYNTHESES METHODS TO INFORM DECISION MAKING ABOUT OPIOID USE AND GENDER-AFFIRMING CARE - Miroshnychenko, Anna (My University, 2025)
Opioid crisis in North America called for an evidence synthesis to compare the effects of analgesics for the management of acute dental pain. Uncertainty about the effects of gender-affirming interventions required a series of systematic reviews and meta- analyses. We used standard, intermediate, and advanced methods to create these evidence syntheses. This thesis presents four systematic reviews that address a total of 44 comparisons, 54 outcomes, 185 included studies. In terms of advanced methods, the best available evidence assessing the comparative effectiveness of acetaminophen, NSAIDs and opioids, ranging from moderate to high certainty, was derived from numerous RCTs, and we performed a systematic review and network meta-analysis. We used Grading of Recommendations Assessment, Development and Evaluation (GRADE) guidance for network meta-analyses and used an automated tool to rate the certainty of the evidence for direct, indirect, and network estimates of effect. For data interpretation and clarity of presentation, we classified the interventions from the most to the least effective by considering the estimate of effect and the certainty of the evidence and organized these data according to a colour coding system. Based on moderate and high certainty evidence, our systematic review and network meta- analysis demonstrated that NSAIDs with or without acetaminophen result in better pain-related outcomes than opioids with or without acetaminophen. As numerous outdated systematic reviews and meta-analyses about the effects of corticosteroids have been published, for our systematic review, we searched the Epistemonikos database and the Living Overview of Evidence (LOVE) platform that utilizes artificial intelligence. With low and very low certainty evidence, our systematic review and meta-analysis suggested that there is a trivial (unimportant) difference in postoperative pain intensity and postoperative infection after administration of corticosteroids orally, submucosally, or intra-muscularly compared to placebo in patients undergoing third molar extractions. Research about gender dysphoria has been a subject of contentious discussion. Therefore, when conducting systematic reviews and meta-analyses about gender-affirming hormone therapy and gender-affirming mastectomy for individuals experiencing gender dysphoria, we devised a plan for minimization and management of conflicts of interest to demonstrate the integrity of our work. The systematic reviews and meta-analyses about the interventions to manage gender dysphoria in children and young adults showed that the current best available evidence about the effects of gender-affirming hormone therapy and mastectomy comes mostly from the methodologically limited before-after and case series studies, and ranges from high to very low certainty. As the fields of dentistry and gender medicine are advancing rapidly, researchers are challenged with creating and appropriately using methods for synthesizing evidence into systematic reviews and (network) meta-analyses to produce authentic results.